Multiplex analysis of serum hormone and cytokine in patients with cervical cOPLL: towards understanding the potential pathogenic mechanisms. (3rd September 2017) - Cai, Guo-Dong; Zhu, Zhuang-Chen; Wang, Jun-Qin; Chen, Guang; Wang, Zeng; Yang, Chen-Song; Sun, Gui-Xin
Abstract: Cervical ossification of the posterior longitudinal ligament (cOPLL) is one of the major causes of myelopathy. However, the mechanism underlying remains elusive. In the present study, using MILLIPLEX magnetic bead panel, we investigated four serum hormones and six serum cytokines in cOPLL patients and healthy subjects. The results showed that tumor necrosis factore-α (TNF-α) were significantly increased, and DDK-1 was significantly decreased in the serum from male and female cOPLL patients compared with those from healthy controls, respectively. Osteopontin (OPN) and fibroblast growth factor-23 (FGF-23) were significantly increased in male cOPLL patients compared with that in healthy male controls. Further analysis showed that FGF-23 and OPN significantly increased, dickkopf-1 (DKK-1) decreased in the extensive cOPLL group. In addition, a significant positive correlation between the OPN and FGF-23 was observed in male cOPLL patients. The results are useful for understanding the mechanism underlying cOPLL.